Discussion Analysis of Abolishing Patent Rights for Covid-19 Vaccine - Rima Diah Pramudyawati (Eduvest - Journal of Universal Studies, 2022)
This study outlines the emergence of discourse in the discourse of the abolition of the Covid-19 vaccine patent which is currently developing in a number of countries. On the one hand, those who are pro against the discourse have a number of arguments that underlie this view, such as the urgency of the need for massive and rapid vaccine production and on the pretext of ensuring global health aspects. Then on the other hand, those who are against it think that the discourse on the abolition of the Covid-19 vaccine patent is not the right solution because it is feared that it will cause disappointment from pharmaceutical companies and related parties and because this is an aspect that is the responsibility of the state. and has been regulated in legal instruments in the field of intellectual property. Meanwhile, the theoretical perspective used refers to the discourse theory proposed by Ernesto Laclau and Chantal Mouffe. In addition, the research method referred to is a qualitative method using a literature study technique on related scientific sources.